Analisis Energi Pembangkit Listrik Tenaga Uap (PLTU) Dual Fuel Line 2 Pt Riau Andalan Pulp And Paper (RAPP) 100 MW Pangkalan Kerinci - Samuel Siregar; Romy Romy; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The Steam Power Plant is one of the largest electric energy provider in Indonesia. In general, the performance of a power plant was evaluated by using the first law of thermodynamics (conservation of energylaw). The first law of thermodynamics only examined the quantity of energy consumption. The purpose of this study is to analyze the work of components, incoming heat, and also nett work from the system so that the energy value of the system is obtained in the form of energy efficiency from the cycle of PT RAPP's 100 MW Steam Power Plant. From the results obtained, pump I work is 0.0047 MW, followed by pump II 1.35 MW, heat is198.27 MW, turbine work is 87.09 MW, and net work is 85.73 MW, so thermal efficiency at PT RAPP steam power plant is 43.24%.Keywords : steam power plant, energy, thermal efficiency